A Highly Sensitive Giant Magnetoresistive (GMR) Biosensor Based on the Magnetic Flux Concentrator Effect - Hao Sun; Jiao Li; Changhui Zhao; Chunming Ren; Tian Tian; Chong Lei; Xuecheng Sun (Micromachines)
Magnetic biosensors have wide applications in biological target detection due to their advantages such as low background noise, convenient detection, and low requirements for sample pretreatment. However, existing magnetic biosensors still have the drawback of low sensitivity compared to optical and electrochemical biosensors. This paper presents the novel design of a high-sensitivity magnetic biosensor by utilizing the magnetic field line convergence effect, which was applied to bacterial detection. The results indicate that it can achieve a detection limitation of 10 CFU/mL, demonstrating that it can be implemented in high-sensitivity biological target detection.